2015
DOI: 10.1186/s40623-015-0301-4
|View full text |Cite
|
Sign up to set email alerts
|

Method for modeling of the components of ionospheric parameter time variations and detection of anomalies in the ionosphere

Abstract: In this study, a new multicomponent model (MCM) to determine the time variation of ionospheric parameters is suggested. The model was based on the combination of wavelets with autoregressive-integrated moving average model classes and allowed the study of the seasonal and diurnal variations of ionospheric parameters and the determination of anomalies occurring during ionospheric disturbances. To investigate in detail anomalous changes in the ionosphere, new computational solutions to detect anomalies of differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 44 publications
3
36
0
Order By: Relevance
“…During the periods of disturbances, anomalous changes are observed in the recorded ionospheric parameters, which indicate the occurrence of anomalous processes in the ionosphere. It is known that the strongest ionospheric disturbances occur during solar events and geomagnetic storms, the study of which has important scientific and applied significance [17][18][19][20][21]. In this paper, based on the joint analysis of the ionosphere parameters and GCR data on the eve of magnetic storms, anomalous increases in variations in the intensity of cosmic rays and the increase in the electron density of the ionosphere that arise during these periods are likely to be associated with the approaching events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the periods of disturbances, anomalous changes are observed in the recorded ionospheric parameters, which indicate the occurrence of anomalous processes in the ionosphere. It is known that the strongest ionospheric disturbances occur during solar events and geomagnetic storms, the study of which has important scientific and applied significance [17][18][19][20][21]. In this paper, based on the joint analysis of the ionosphere parameters and GCR data on the eve of magnetic storms, anomalous increases in variations in the intensity of cosmic rays and the increase in the electron density of the ionosphere that arise during these periods are likely to be associated with the approaching events.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the computational solutions proposed in [18], we determine the values of wavelet coefficients that exceed a given threshold:…”
mentioning
confidence: 99%
“…Among the general approaches we can emphasize the traditional moving median method [1,9], empirical models of the ionosphere [2,3,[5][6][7], application of neural networks [2,8,10], and wavelet transform [10][11][12][13][14]. The most developed empirical model of the ionosphere is the International Reference Ionosphere (IRI) model [5], which is based on a wide range of ground and space data.…”
Section: Introductionmentioning
confidence: 99%
“…In the paper, we use a complex approach based on wavelet transform methods and their combinations with classical autoregressive approaches and neural networks. In the previous papers [4,[12][13][14] we showed that application of classical autoregressive methods [15] in combination with modern methods for pattern recognition allow us to obtain quite exact estimates and they are easily realized in automatic mode. The main advantage of the suggested approach is the mathematical validity and, as a consequence, the possibility to receive the results with defined confidence probability.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is important to model the ionospheric parameters to extract the main characteristics of ionospheric disturbances. Mandrikova et al (2015) have developed an algorithm for modeling ionospheric parameter FoF2 and extracting the main characteristics of ionospheric perturbations during different seasons and geomagnetic activities.…”
mentioning
confidence: 99%